The New Realities : In Government and Politics, In Economy and Business, In Society and In World View - Drucker, Peter F. , 1909-2005 (New Delhi Butterworth-Heinemann, An Imprint of Elsevier, 2004)
Include Index
Keywords: Social history -- 1970- -- World politics -- 1945- -- Economic history -- 1971-1990